210k views
6 votes
How do you solve -4 + y = 6 and y= 7x - -6 by substitution?

User Jayson Ash
by
6.5k points

2 Answers

10 votes

Answer:

x=4/7 and y=10

Explanation:

To solve for x, we must isolate y in one of the equations to then insert it into the other equation. We can take the first equation, -4 + y = 6, and add 4 to both sides. This gives us y = 4+6, or y = 10. Since y is a variable, we can subsititute 10 into the second equation, y = 7x - (-6), giving us 10 = 7x - (-6). The minus negative six is equal to plus six. This gives us 10 = 7x +6. Now we can solve for x. Subtract 6 from both sides; 4 = 7x. Now to find x, we have to divide both sides by 7. This gives us x = 4/7.

User MasterScrat
by
6.2k points
5 votes

Answer:

by doing the math

Explanation:

do (7x)-(-6) then the other problem and find out witch one is more

User Andrew Barnett
by
5.8k points